Electronegativity and Hardness: Linear Isoelectronic Trends - Upadhyay, Dinesh P. (Current Physical Chemistry, 2017)
Background: Excellent linear correlations exist between isoelectronic values of square root of the electronegativity measure i.e. (I+A)/21/2 and the measure of hardness, (I-A)/2 in eight out of the first ten isoelectronic sequence (H-Ne); the determination coefficients are nearly one. Method: For He and Ne isoelectronic series, with inert gas configuration, the plots between (I+A)/21/2 and (I-A)/2 are found to be nonlinear. For these two, linear plots exist between (I+A)/2 and (I-A)/2. Within the purview, the present study supports the recent suggestion that if (I+A)/2 and (I-A)/2 are to serve as the electronegativity and the hardness measure respectively, the mutual relation between electronegativity and hardness would depend on the electronic configuration of the neutral species. In majority of the cases, proportionality would exist between the square root of the electronegativity measure i.e. (I+A)/21/2 and the hardness measure, (IA)/2, except for the species with inert gas configuration. Conclusion: The (I+A)/21/2 vs. (I-A)/2 plots are very useful in pointing out the accuracy of listed ionization potentials. In Fluorine isoelectronic series, an abrupt inconsistency has been observed that has been linked up with incorrectly listed handbook value of VI ionization potential of Phosphorous.
Keywords: Atomic number